Peraturan Desa Dalam Kedudukan Dan Pengujian Konstitusionalitas Perspektif Peraturan Perundang-Undangan Indonesia - Sukimin, Sukimin; Nuswanto, Heru; Triwati, Ani (JURNAL USM LAW REVIEW, 2023)
The purpose of this writing is to analyze the position of Village Regulations in statutory regulations and to formulate a form of reviewing the constitutionality of Village Regulations in statutory regulations. The novelty of previous research is that this research does not only emphasize the position of village regulations but also examines the constitutionality of village regulations in a combined form. The Village Head and the Village Consultative Body have the authority and independence from village institutions to regulate life with the community through regulatory instruments in the form of village regulations. The existence or position of village regulations in the legal system in Indonesia is not listed in the hierarchy of statutory regulations, so that the form of reviewing the constitutionality of village regulations is unclear. Of course, this is interesting to study in more depth regarding how the position of village regulations is in statutory regulations and also how the form of testing the constitutionality of village regulations in statutory regulations. Through the method of research on doctrinal law or normative law, this research has the object of studying legal norms or rules as a building system related to a legal event. The position of village regulations also includes statutory regulations which are recognized juridically, while related to testing the constitutionality of village regulations, namely in the form of executive review by carrying out supervision which authority is given to the regent/mayor to supervise, besides that the regent/mayor can also cancel village regulations if they conflict with higher regulations and/public interest. Tujuan dari penulisan ini yaitu untuk menganalisis kedudukan peraturan desa dalam peraturan perundang-undangan serta merumuskan bentuk pengujian konstitusionalitas peraturan desa dalam peraturan perundangundangan. Kebaruan dari penelitian sebelumnya bawasanya penelitian ini tidak hanya menekankan pada kedudukan dari peraturan desa melainkan juga kepada pengujian konstitusionalitas peraturan desa dalam bentuk kombinasi. Kepala desa beserta Badan Permusyawaratan Desa memiliki wewenang dan kemandirian dari lembaga desa dapat mengatur kehidupan bersama masyarakat melalui instrumen aturan yang dalam bentuk peraturan desa. Keberadaan atau kedudukan peraturan desa dalam sistem hukum di Indonesia tidak tercantum dalam hierarki peraturan perundang-undangan, sehingga bentuk pengujian konstitusionalitas peraturan desa menjadi tidak jelas. Tentunya hal tersebut menarik untuk dikaji lebih mendalam terkait bagaimana kedudukan peraturan desa dalam peraturan perundang-undangan dan juga bagaimana bentuk pengujian konstitusionalitas peraturan desa dalam peraturan perundang-undangan. Melalui metode penelitian hukum doktrinal atau hukum normatif, maka penelitian ini mempunyai objek kajian terhadap kaidah atau aturan hukum sebagai suatu bangunan system yang terkait dengan suatu peristiwa hukum. Kedudukan peraturan desa termasuk pula sebagai peraturan perundang-undangan yang diakui secara yuridis keberadaaanya, Sedangkan terkait dengan pengujian konstitusionalitas peraturan desa yaitu dalam bentuk executive review dengan melakukan pengawasan yang kewenangan diberikan kepada bupati/walikota untuk mengawasi, selain itu pula bupati/walikota dapat pula membatalkan peraturan desa apabila bertentangan dengan peraturan yang lebih tinggi dan/kepentingan umum